BIM: A COLLABORATIVE APPROACH TO ARCHITECTURAL PROJECT MANAGEMENT - Nawal Benmicia; Lakhdar Belarbi (International Journal of Innovative Technologies in Social Science, 2024)
At the present time, digital technology has fundamentally altered both our daily lives and professional environments. New tools and software have emerged, becoming crucial across various fields, including urban development, by replacing traditional methods. Among these technological advancements is Building Information Modeling (BIM), also known as Better Information Management, which has evolved into a collaborative management process integrating architectural projects.BIM relies on technologies and solutions that intelligently model and structure the different stakeholders involved in a project. It creates a virtual environment that accurately represents buildings and urban spaces, including their geometry, spatial organizations, functionalities, and other significant information.This contribution aims to examine the challenges associated with using BIM as a collaborative project management process in architecture. It also seeks to explore new strategies that promote the efficiency and quality of architectural projects.